Reasons for the exclusion of women from leadership positions in three private schools in Francistown, Botswana - Kawonde, Enia (Midlands State University, 2018)
This study examined the reasons for the exclusion of women in leadership in three Botswana private schools found in the city of Francistown. In this study, a case study design was used as a strategy to conduct the practical aspects of this research. The study was informed by the mixed method research design. Interviews and questionnaires were research tools that were used to collect data for this study. Questionnaires had closed and open ended questions. The population comprised of three English medium schools in Francistown, Botswana. The sample consisted of three administrators and twenty teachers. Some reasons that hinder women from attaining leadership positions were identified. Inadequate financial resources and time constraints incapacitated the researcher in doing a national study. Further research at a larger scale is highly recommended to refute or to affirm the results of this study.